2018
DOI: 10.7589/2017-05-109
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Outcomes of Snake Fungal Disease in Free-ranging Pygmy Rattlesnakes (Sistrurus miliarius)

Abstract: Snake fungal disease (SFD) is caused by the fungus Ophidiomyces ophiodiicola and its documentation in wild snake populations has risen sharply in the past decade. Little is known regarding the fate of individual, free-ranging snakes afflicted with SFD. We monitored an afflicted population of pygmy rattlesnakes ( Sistrurus miliarius) at Lake Woodruff National Wildlife Refuge in Central Florida, US for 2 yr. The severity of SFD in individual snakes was unrelated to the probability of their recapture later in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Further research is required to determine the relative importance of these factors and others such as host taxonomy, life history, habitat degradation, food availability, environmental conditions (eg, temperature), season, and stress, as well as inoculation route and dose on disease development. 4,17,23,24,26,27,29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is required to determine the relative importance of these factors and others such as host taxonomy, life history, habitat degradation, food availability, environmental conditions (eg, temperature), season, and stress, as well as inoculation route and dose on disease development. 4,17,23,24,26,27,29…”
Section: Discussionmentioning
confidence: 99%
“…17,24,26,40 However, the relative effects of brumation, environmental temperature, and nutritional status on the pathogenesis of ophidiomycosis, including aspects of transmission, are unknown. 23,26 Ophidiomyces ophiodiicola was demonstrated as the causative agent of fungal disease in snakes through experimental studies using 2 different models. 2,27 The first study introduced the fungus into the nasolabial pits of cottonmouths (Agkistrodon piscivorus) using a catheter.…”
mentioning
confidence: 99%
“…Snake Fungal Disease (SFD) is caused by a severe cutaneous infection with the fungus Ophidiomyces ophiodiicola and was first seen in North America in 2006 [ 2 ]. This fungus has since been observed infecting the epidermis of 23 snake species, causing severe SFD and mortality in at least 3 of them [ 3 ], although one other snake species readily recovers from this cutaneous infection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several investigations have been conducted determining the physiological impact of ophidiomycosis on pygmy rattlesnakes ( Sistrurus miliarius ) in Florida. Specifically, snakes with ophidiomycosis have shown a decrease in body condition with increasing severity of infection, but severity was not associated with recapture rate, and severely affected snakes apparently cleared infection [ 54 ]. It was also observed that the resting metabolic rate in this species was increased in ophidiomycosis-positive individuals, which may contribute to declining individual health during the disease process [ 55 ].…”
Section: Discussionmentioning
confidence: 99%